A model of cell growth and possibilities of tumour treatment by selective protein depletion - Tepic, Slobodan; Pyk, Paweł (Zielona Góra: Uniwersytet Zielonogórski)
A simple model of a self-enlarging synthesizing unit with the growth-limiting assumptions on precursor transport losses and product turnover is used as a prototype dynamic system for a cell growth model. The model successfully describes the main features of cell growth and allows for a rational discussion of the cell cycle. The cell is viewed as a non-linear capacitance damped by transport losses.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka